Pentecostais na política capixaba : representação parlamentar da Igreja Assembleia de Deus nas eleições (2002, 2006, 2010) - Carneiro, Washington Phillip Spanhol (2013)
The present dissertation, sought to observe the presence of candidates of the Evangelical Church Assembly of God in the state of Espírito Santo within of their parliamentary representation in state legislature elections in 2002, 2006 and 2010. Was observed the relation between religion and politics highlighting the evangelical pentecostal expansion, specifically the case of the Assembly of God. The study departs from the idea that the choice of leaders within religious institutional structures may also influence choices within social structures, for example, the choice of political leaders.